2019
DOI: 10.2147/ppa.s201054
|View full text |Cite
|
Sign up to set email alerts
|

<p>Engaging patients and informal caregivers to improve safety and facilitate person- and family-centered care during transitions from hospital to home &ndash; a qualitative descriptive study</p>

Abstract: Purpose: The purpose was to describe patients and informal caregivers’ perspectives on how to improve and monitor care during transitions from hospital to home as part of a larger research study to prioritize the components that most influence the development of successful care transition interventions. Methods: We conducted a qualitative descriptive study between July and August 2016, during which time semi-structured telephone interviews (n=8) were completed with patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
3
26
0
3
Order By: Relevance
“…Studies have documented the complex but indispensable role informal caregivers play in care coordination and highlight how family presence when reviewing discharge instructions can help reinforce, clarify and improve adherence. 19,20 The importance that perceived relationships with health care providers may play in the patient's level of engagement and adherence to instructions has previously been described as important for adherence to medications. 21 This factor is of timely importance given recent work showing that both inpatient and outpatient physicians rarely feel responsible for patient care and adherence after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented the complex but indispensable role informal caregivers play in care coordination and highlight how family presence when reviewing discharge instructions can help reinforce, clarify and improve adherence. 19,20 The importance that perceived relationships with health care providers may play in the patient's level of engagement and adherence to instructions has previously been described as important for adherence to medications. 21 This factor is of timely importance given recent work showing that both inpatient and outpatient physicians rarely feel responsible for patient care and adherence after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Poor communication in the health-care system, generally (not just during care transitions), is a common problem expressed by many patients and their caregivers, 41 typically those who have multiple chronic conditions, 42 require significant health care and interact with various care providers across settings. 43 Care transitions, in particular, are a heightened time of vulnerability for patients and their caregivers. 44 In our research, we found that poor communication was par- is too long, patient and caregivers can become confused and frustrated.…”
Section: Communicating Uncertaintymentioning
confidence: 99%
“…Australia and the United Kingdom have developed national standards for electronic DSs [ 18 , 28 ], and Canadian researchers have explored standardizing DSs in Nova Scotia [ 29 ]. In contrast, most US research aimed at increasing patient safety during care transitions focuses upon improving discharge planning processes (eg, training clinicians to generate more useful discharge documentation [ 30 , 31 ] or involving patients and caregivers in discharge planning [ 31 , 32 ]).…”
Section: Discussionmentioning
confidence: 99%